Uncovering the Structure Complexity of Stakeholder Interactions with Process and Product Innovation in Oil and Gas EPC Projects - ALHAMMADI, NASSER MOHAMED IBRAHIM (2021)
Using Social Network Analysis framework to analyse the influence of project stakeholders on process and product innovation, this study set out to understand the stakeholders and activities that can lead to process and product innovation in a Greenfield, Downstream Oil and Gas EPC project. Deriving their position from having a high number of interactions and occupying a central position in social network, the Engineering Manager, the Cost Control Manager/ Procurement Engineer, and the Senior Construction Engineer were identified as the most influential stakeholders in Process Innovation in the Engineering, Procurement and Construction Phases respectively. For the same reasons, the Engineering Manager, Cost Control Manager/Procurement Engineer, and Senior Quality Assurance/ Quality Control Engineer were identified as the most influential stakeholders on product innovation in the Engineering, Procurement and Construction Phases, respectively. Based on being the most senior decision maker in the whole EPC project, Engineering Manager was found to have the highest level of influence on process innovation. For the same reasons, the Project Manager was identified as most influential stakeholder on product innovation. In terms of activity nodes, the most influential on both process and product innovation were identified as those having many connections with other nodes giving them access to important information flows. The most influential activity nodes on process innovation were identified as “IPF (SIL Review)” for Engineering, “Weekly Procurement expediting meetings with Contractor and Vendors” for Procurement, and “Fire water Tank – Final Testing” for the Construction Phase. Also based on the number of node connections, the most influential activities on product innovation were identified as: IPF (SIL Review) for Engineering, “Suction K.O. drum – prepare and Issue MR” for Procurement, and “Mechanical (Equipment) – HIPS Installation” for the Construction Phase. Because of its high number of connections, highly central Network position, and ranking higher in the hierarchy in terms of decision making, “IPF (SIL Review)” was identified as the most influential activity on both Process and Product innovation for the entire EPC project.